Labor Absorption in Agribusiness of Patchouli Plant in Benua Village, Konawe Selatan - Rosmayani Rosmayani; Ilma Sarimustaqyima Rianse; Fahria Nadiryati Sadimantara (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2022)
The aim of this study is to understand the role of patchouli agribusiness in the absorption of employment in Benua Villages, Benua districts, South Konawe regency. These research was carried out in continent village, Continent District, South Konawe Regency. The population in this study were, namely agribusiness in Benua villages that do patchouli farming, patchouli oil business, and workers totaling 35 people, with a sample of 35 people because all the population was sampled. The variables in this study are the identity of the respondents including: farmer's age, level of education, patchouli management experience, and the number of family dependents. The results of this study showed that the cultivation of patchouli, patchouli oil, and labor has employment absorption of 20%